Velocity modelling for pipeline inspection gauge - Low, Zi Li; Masli Irwan Roslia,; Panuh, Dedikarni (Penerbit Universiti Kebangsaan Malaysia, 2019)
Pipeline inspection gauges (PIGs) apply in oil and gas industries, particularly in cleaning, dewatering, and inspecting pipelines. Also, both the speed and driving pressure for the PIGs operation are deduced basis on the guesswork or experience. In this study, the dynamic behaviour of PIGs in gas pipelines is investigated. The dynamic differential equations of PIG velocity are used to calculate the motion of models Solghar and Nieckele. Differential and other conditional equations are simultaneously solved by using the ODE45 built-in function of the MATLAB® software. Generally, the dynamic motion of PIGs depends on the differential pressure of the fluid and can be affected by other parameters, such as bypass area and frictional force. Therefore, we further examine and consider these parameters in modelling. We validate the modelling results by comparing them with the experimental results obtained by a PIG manufacturing company. Results show that the Solghar model is more suitable than Nieckele model in operating condition selections. The increasing bypass area and frictional force reduce the movement speed of the PIG because of the decrease in the pressure difference between the PIGs. Subsequently, a graphical user interface is created and customised in MATLAB® to automate the calculation of PIG velocity.